Preparation process of coal gangue aggregate 3D printing concrete material
By treating aluminum sulfate and ethyl orthosilicate of fine aggregates of coal gangue, combined with the use of modified red brick fine powder, the problem of insufficient strength and fluidity of coal gangue in 3D printed concrete is solved, and the structure of concrete is significantly improved Strength and printing performance.
Patent Information
- Application Number
- CN202411362186.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
AI Technical Summary
In 3D printed concrete, coal gangue decreases structural strength and low fluidity due to high porosity, and the increase in pores after calcination treatment leads to poor printing properties.
After the coal gangue fine aggregate is treated with saturated aluminum sulfate solution and ethyl orthosilicate, it is heated and calcined by saturated lime water to form calcium sulfate and aluminum hydroxide to fill pores, hydrolyzed to form nano-hydrated calcium silicate, increasing the strength of the aggregate , and reduce water absorption by modifying red brick micropowder to improve the strength of concrete structure.
It improves the compactness and strength of coal gangue fine aggregates, improves the flowability and printing properties of concrete, enhances the overall strength of concrete structures, and overcomes the problem of strength reduction caused by high porosity.
Smart Images

Figure CN119143449A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing concrete preparation, and in particular to a preparation process of gangue aggregate 3D printing concrete material. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Concrete material is one of the most important building materials in today's society. 3D printing concrete technology is an additive construction technology based on 3D printing technology, which uses concrete slurry as printing material. Since this technology can be automatically, quickly and accurately printed through software program control, it not only significantly improves the utilization rate of concrete and reduces material waste, but also shortens the construction period and reduces the construction cost. In addition, 3D printing concrete technology can also print various special-shaped and complex concrete structures, thereby achieving personalized customization and meeting some special technical requirements, which is unmatched by traditional concrete structure construction technology.
[0004] Gangue is a solid waste with low carbon content that cannot be used as fuel and is produced during coal mining, washing, coal mine construction, and development and excavation. Its annual emissions account for about 10% of the coal production of the year. my country's coal production ranks first in the world. Not only is there a large amount of stockpiled gangue, but hundreds of millions of tons of new gangue are produced every year, which has brought many adverse effects on the environment. Realizing the resource utilization of industrial solid waste such as gangue is an important part of coal mining enterprises to achieve green and sustainable development. Adding gangue to concrete materials instead of natural sand and gravel aggregates is an effective way to utilize it, but because gangue contains some organic matter, the concrete prepared from it has poor volume stability and is prone to cracking during service. For this reason, gangue is usually calcined before being used as concrete aggregate. However, the pores in calcined gangue increase due to the volatilization of organic matter. When it is used as aggregate for 3D printed concrete materials, it not only causes the fluidity of the concrete to be lower and the printability to deteriorate, but also causes the strength of the prepared concrete structure to decrease. Summary of the invention
[0005] In view of the above problems, the present invention provides a preparation process of gangue aggregate 3D printing concrete material, which not only alleviates the adverse effect of calcined gangue on the fluidity of 3D printing concrete material, but also improves the strength of the prepared concrete structure. Specifically, the technical solution of the present invention is as follows.
[0006] A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) The coal gangue fine aggregate which has been calcined to remove organic matter is immersed in a saturated aluminum sulfate solution, and the fine aggregate is separated after standing. After drying, the fine aggregate is immersed in anhydrous ethanol containing saturated ethyl orthosilicate and allowed to stand. After completion, the fine aggregate is separated and dried to obtain coal gangue fine aggregate a.
[0007] (2) Spraying saturated lime water into the gangue fine aggregate a under stirring conditions, heating and keeping the formed wet material in a closed container, and calcining the material after the reaction is completed to obtain modified gangue fine aggregate.
[0008] (3) Mix silicate cement, modified coal gangue fine aggregate, coarse aggregate, admixture, water reducer, and chopped fibers, then add water and mix evenly to obtain the 3D printing concrete material.
[0009] Furthermore, in step (1), the ratio of the coal gangue fine aggregate to the saturated aluminum sulfate solution is 1 g: 5-20 ml. Optionally, the particle size of the coal gangue fine aggregate is 1-2 mm.
[0010] Furthermore, in step (1), the fine aggregate is separated after standing for not less than 30 minutes. Optionally, the drying temperature is 60-100°C and the drying time is 20-30 minutes.
[0011] Furthermore, in step (1), the ratio of the fine aggregate to anhydrous ethanol is 1 g: 5-20 ml. Optionally, the standing time in the anhydrous ethanol is not less than 40 min.
[0012] Furthermore, in step (1), the drying temperature is 50-70° C. and the drying time is 10-15 min.
[0013] Furthermore, in step (2), the ratio of the coal gangue fine aggregate a to saturated lime water is 1g:0.45-0.6ml.
[0014] Furthermore, in step (2), the heating temperature is 60-80° C., and the insulation time is 8-10 hours.
[0015] Furthermore, in step (2), the calcination treatment is carried out at a temperature of 600-720° C. and for a time of 1-1.5 hours.
[0016] Furthermore, in step (3), the proportions of the silicate cement, modified coal gangue fine aggregate, coarse aggregate, admixture, water reducer, and chopped fibers are 30-50 parts by weight: 60-92 parts by weight: 125-180 parts by weight, 4-10 parts by weight: 0.7-1.1 parts by weight: 5-7 parts by weight, and the water is added at a water-cement ratio of 0.38-0.45.
[0017] Furthermore, in step (3), the water reducer includes any one of a polycarboxylate water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, and the like.
[0018] Furthermore, in step (3), the chopped fibers include at least one of polyethylene fibers, polypropylene fibers, polyvinyl alcohol fibers, polyacrylonitrile fibers, basalt fibers, etc. Optionally, the length of the chopped fibers is 3 to 10 mm.
[0019] Furthermore, in step (3), the admixture includes at least one of mineral powder, shell powder, modified waste red brick powder, waste glass powder, etc. Optionally, the fineness of the admixture is 200-350 mesh.
[0020] Furthermore, the modified waste red brick powder is prepared by the following method: placing the waste red brick powder in saturated lime water, separating the waste red brick powder after sufficient absorption, then adding aluminum nitrate solution and stirring evenly, and drying the obtained mixture to obtain the modified waste red brick powder.
[0021] Furthermore, the ratio of the waste red brick powder to saturated lime water is 1g: 10-30ml. Optionally, the waste red brick powder is placed in saturated lime water and then left to stand for 20-30 minutes so that the red brick powder can fully absorb the saturated lime water.
[0022] Furthermore, the ratio of the waste red brick powder to the aluminum nitrate solution is 1g: 0.4-0.6ml. Optionally, the mass fraction of the aluminum nitrate solution is 2-5%.
[0023] Furthermore, the drying temperature is 60-80° C., and the mixture is dried to a constant weight at this temperature.
[0024] Compared with the prior art, the present invention has at least the following beneficial technical effects: The present invention first absorbs aluminum sulfate and ethyl orthosilicate in the calcined coal gangue fine aggregate, and then further heats and insulates the coal gangue fine aggregate using saturated lime water. The aluminum sulfate reacts with saturated lime water to form calcium sulfate and aluminum hydroxide to fill the pores in the coal gangue fine aggregate, which not only reduces the porosity but also helps to improve the strength of the aggregate. At the same time, the ethyl orthosilicate is hydrolyzed in the alkaline environment provided by saturated lime water to form nano silicon dioxide, which further reacts with calcium hydroxide in saturated lime water to form nano calcium silicate hydrate (CSH), which fills the pores in the fine aggregate densely. After calcination, the aluminum hydroxide is converted into active nano alumina, and the nano calcium silicate hydrate is dehydrated. After the gangue fine aggregate treated as above enters the concrete, it not only avoids the problem of low fluidity and poor printability of the concrete, but also the active nano-alumina reacts with the hydration product calcium hydroxide in the silicate cement to form a hydrated calcium aluminate cementitious product, and the dehydrated nano-calcium silicate can react again under the action of mixing water in the concrete to form a hydrated calcium silicate with cementitious properties. The product with cementitious properties formed by the above-mentioned double "secondary hydration reaction" not only effectively improves the compactness of the gangue fine aggregate and increases the strength, but also increases the bonding force between the gangue fine aggregate and the concrete matrix, improves the overall strength of the printed concrete structure, and overcomes the problem of reduced strength of the concrete structure caused by the high porosity of the gangue. In addition, the present invention also prepares a modified admixture with red brick micropowder, a construction solid waste, to overcome the problem that the high water absorption rate of the red brick micropowder causes the reduced fluidity of the 3D printed concrete and the insufficient cement hydration, thereby causing the reduced strength of the concrete structure. This is because the present invention first loads saturated lime water in the pores of red brick micropowder, and then reacts to form aluminum hydroxide and calcium nitrate after adding aluminum nitrate solution, wherein the aluminum hydroxide can fill and compact the pores in the red brick micropowder particles to reduce water absorption. At the same time, the calcium nitrate as an early strength agent also helps to promote the hydration reaction of cement, improve the early strength of the concrete structure after printing, and reduce the structural deformation caused by the deadweight of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 The following is a graph showing the compressive strength test of the 3D printed concrete specimen of Example 1.
[0027] Figure 2 This is a flowability test diagram of the 3D printed concrete material of the following Example 1.
[0028] Figure 3This is a compressive strength test diagram of the 3D printed concrete specimen of the following Example 2. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0030] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with specific embodiments.
[0031] Example 1 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) calcined to remove organic matter with a saturated aluminum sulfate solution at a ratio of 1 g: 15 ml, let it stand for 40 minutes, filter out the fine aggregate, and dry it at 80°C for 20 minutes. Then mix the obtained fine aggregate with anhydrous ethanol containing saturated ethyl orthosilicate at a ratio of 1 g: 10 ml and let it stand for 60 minutes. After completion, filter out the fine aggregate and dry it at 60°C for 12 minutes to obtain coal gangue fine aggregate a for standby use.
[0032] (2) Spray saturated lime water into the gangue fine aggregate a at a ratio of 1 g:0.5 ml while stirring, place the resulting wet material in a sealed reactor, heat it in a water bath to 75° C. for 8 hours, and calcine at 650° C. for 1 hour after the reaction is completed to obtain modified gangue fine aggregate for later use.
[0033] (3) Take 45 parts by weight of 42.5 ordinary Portland cement, 70 parts by weight of the modified coal gangue fine aggregate of this embodiment, 148 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 6 parts by weight of 350-mesh shell powder, 0.85 parts by weight of polycarboxylic acid water reducer, and 4 parts by weight of polypropylene fiber with a length of 5 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.41 and stir evenly to obtain 3D printing concrete material.
[0034] After printing, the 3D printed concrete material prepared in this embodiment was cut out of the specimen, and then the 1d and 28d compressive strengths were tested according to the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T 50081-2019) (the test process is as follows Figure 1 In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005) (the testing process is as shown in Figure 2 The results are as follows: 1d compressive strength = 9.34MPa, 28d compressive strength = 48.57MPa, fluidity = 17.6cm.
[0035] Example 2 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) after calcination to remove organic matter with a saturated aluminum sulfate solution at a ratio of 1 g: 5 ml, let it stand for 30 minutes, filter out the fine aggregate, and dry it at 60° C. for 20 minutes. Then mix the obtained fine aggregate with anhydrous ethanol containing saturated ethyl orthosilicate at a ratio of 1 g: 5 ml and let it stand for 40 minutes. After completion, filter out the fine aggregate and dry it at 50° C. for 10 minutes to obtain coal gangue fine aggregate a for standby use.
[0036] (2) Spray saturated lime water into the gangue fine aggregate a at a ratio of 1 g:0.45 ml while stirring, place the resulting wet material in a sealed reactor, heat it in a water bath to 60° C. for 10 hours, and calcine at 720° C. for 1 hour after the reaction is completed to obtain modified gangue fine aggregate for later use.
[0037] (3) Place 200-mesh waste red brick powder in saturated lime water at a ratio of 1 g:10 ml, filter out the waste red brick powder after standing for 30 min, then add 2% by mass aluminum nitrate solution at a ratio of 1 g:0.6 ml and stir evenly, and dry the resulting mixture at 80°C to constant weight to obtain modified waste red brick powder.
[0038] (4) Take 30 parts by weight of 42.5 ordinary Portland cement, 60 parts by weight of the modified coal gangue fine aggregate of this embodiment, 125 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 4 parts by weight of the modified waste red brick powder of this embodiment, 0.7 parts by weight of polycarboxylic acid water reducer, and 5 parts by weight of polyvinyl alcohol fiber with a length of 10 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.38 and stir evenly to obtain 3D printing concrete material.
[0039] After printing, the 3D printed concrete material prepared in this embodiment was cut out of the specimen, and then the 1d and 28d compressive strengths were tested according to the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T 50081-2019) (the test results are shown in Figure 3 In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 11.63MPa, 28d compressive strength = 52.42MPa, and fluidity = 16.9cm.
[0040] Example 3 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) after calcination to remove organic matter with a saturated aluminum sulfate solution at a ratio of 1 g: 20 ml, let it stand for 35 minutes, filter out the fine aggregate, and dry it at 100°C for 30 minutes. Then mix the obtained fine aggregate with anhydrous ethanol containing saturated ethyl orthosilicate at a ratio of 1 g: 20 ml and let it stand for 50 minutes. After completion, filter out the fine aggregate and dry it at 70°C for 15 minutes to obtain coal gangue fine aggregate a for standby use.
[0041] (2) Spray saturated lime water into the gangue fine aggregate a at a ratio of 1 g:0.6 ml while stirring, place the resulting wet material in a sealed reactor, heat it in a water bath to 80° C. for 9 hours, and calcine it at 600° C. for 1.5 hours after the reaction is completed to obtain modified gangue fine aggregate for later use.
[0042] (3) 220-mesh waste red brick powder was placed in saturated lime water at a ratio of 1 g:30 ml, and the waste red brick powder was filtered out after standing for 20 min. Then, 5% by mass aluminum nitrate solution was added at a ratio of 1 g:0.4 ml and stirred evenly. The obtained mixture was dried at 60°C to constant weight to obtain modified waste red brick powder.
[0043] (4) Take 50 parts by weight of 42.5 ordinary Portland cement, 92 parts by weight of the modified coal gangue fine aggregate of this embodiment, 180 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 10 parts by weight of the modified waste red brick powder of this embodiment, 1.1 parts by weight of sodium lignin sulfonate water reducer, and 7 parts by weight of polyethylene fiber with a length of 3 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.45 and stir evenly to obtain 3D printing concrete material.
[0044] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 11.02MPa, 28d compressive strength = 49.73MPa, and fluidity = 17.4cm.
[0045] Example 4 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: Take 45 parts by weight of 42.5 ordinary Portland cement, 70 parts by weight of coal gangue fine aggregate (particle size distribution between 1 and 2 mm) calcined to remove organic matter, 148 parts by weight of crushed stone coarse aggregate with a particle size of 15 to 20 mm, 6 parts by weight of 350-mesh shell powder, 0.85 parts by weight of polycarboxylic acid water reducer, and 4 parts by weight of polypropylene fiber with a length of 5 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.41 and stir evenly to obtain 3D printing concrete material.
[0046] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 6.81MPa, 28d compressive strength = 42.04MPa, and fluidity = 14.8cm.
[0047] Example 5 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) from which organic matter has been calcined and removed with a saturated aluminum sulfate solution at a ratio of 1 g:15 ml, let it stand for 40 min, filter out the fine aggregate, and dry it at 80° C. for 20 min to obtain coal gangue fine aggregate a for later use.
[0048] (2) Spray saturated lime water into the gangue fine aggregate a at a ratio of 1 g:0.5 ml while stirring, place the resulting wet material in a sealed reactor, heat it in a water bath to 75° C. for 8 hours, and calcine at 650° C. for 1 hour after the reaction is completed to obtain modified gangue fine aggregate for later use.
[0049] (3) Take 45 parts by weight of 42.5 ordinary Portland cement, 70 parts by weight of the modified coal gangue fine aggregate of this embodiment, 148 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 6 parts by weight of 350-mesh shell powder, 0.85 parts by weight of polycarboxylic acid water reducer, and 4 parts by weight of polypropylene fiber with a length of 5 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.41 and stir evenly to obtain 3D printing concrete material.
[0050] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 8.42MPa, 28d compressive strength = 44.67MPa, and fluidity = 16.5cm.
[0051] Example 6 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) after calcination to remove organic matter with a saturated aluminum sulfate solution at a ratio of 1 g: 5 ml, let it stand for 30 minutes, filter out the fine aggregate, and dry it at 60° C. for 20 minutes. Then mix the obtained fine aggregate with anhydrous ethanol containing saturated ethyl orthosilicate at a ratio of 1 g: 5 ml and let it stand for 40 minutes. After completion, filter out the fine aggregate and dry it at 50° C. for 10 minutes to obtain coal gangue fine aggregate a for standby use.
[0052] (2) According to the ratio of 1 g: 0.45 ml, clean water is sprayed into the gangue fine aggregate a while stirring, and the resulting wet material is placed in a sealed reactor and heated to 60° C. in a water bath for 10 hours. After the reaction is completed, the reactor is calcined at 720° C. for 1 hour to obtain modified gangue fine aggregate, which is set aside.
[0053] (3) Take 30 parts by weight of 42.5 ordinary Portland cement, 60 parts by weight of the modified coal gangue fine aggregate of this embodiment, 125 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 4 parts by weight of the modified waste red brick powder of Example 2, 0.7 parts by weight of polycarboxylic acid water reducer, and 5 parts by weight of polyvinyl alcohol fiber with a length of 10 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.38 and stir evenly to obtain 3D printing concrete material.
[0054] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 9.79MPa, 28d compressive strength = 49.06MPa, and fluidity = 17.1cm.
[0055] Example 7 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: Take 50 parts by weight of 42.5 ordinary Portland cement, 92 parts by weight of the modified coal gangue fine aggregate of Example 3, 180 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 10 parts by weight of 220-mesh waste red brick powder, 1.1 parts by weight of sodium lignin sulfonate water reducer, and 7 parts by weight of polyethylene fiber with a length of 3 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.45 and stir evenly to obtain 3D printing concrete material.
[0056] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 8.13MPa, 28d compressive strength = 43.52MPa, and fluidity = 16.2cm.
[0057] Example 8 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Place 200-mesh waste red brick powder in saturated lime water at a ratio of 1 g:10 ml, let it stand for 30 minutes, filter out the waste red brick powder, and dry it at 80°C to constant weight to obtain modified waste red brick powder.
[0058] (2) Take 30 parts by weight of 42.5 ordinary Portland cement, 60 parts by weight of the modified coal gangue fine aggregate of Example 2, 125 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 4 parts by weight of the modified waste red brick powder of this example, 0.7 parts by weight of polycarboxylic acid water reducer, and 5 parts by weight of polyvinyl alcohol fiber with a length of 10 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.38 and stir evenly to obtain 3D printing concrete material.
[0059] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 8.75MPa, 28d compressive strength = 46.65MPa, and fluidity = 15.4cm.
[0060] Example 9 A preparation process of gangue aggregate 3D printing concrete material, comprising the following steps: (1) Mix the coal gangue fine aggregate (with a particle size distribution between 1 and 2 mm) calcined to remove organic matter with a saturated aluminum sulfate solution at a ratio of 1 g: 15 ml, let it stand for 40 minutes, filter out the fine aggregate, and dry it at 80°C for 20 minutes. Then mix the obtained fine aggregate with anhydrous ethanol containing saturated ethyl orthosilicate at a ratio of 1 g: 10 ml and let it stand for 60 minutes. After completion, filter out the fine aggregate and dry it at 60°C for 12 minutes to obtain coal gangue fine aggregate a for standby use.
[0061] (2) Spray saturated lime water into the gangue fine aggregate a at a ratio of 1 g:0.5 ml while stirring, dry the resulting wet material at 75° C. to constant weight, and then calcine at 650° C. for 1 hour to obtain modified gangue fine aggregate for later use.
[0062] (3) Take 45 parts by weight of 42.5 ordinary Portland cement, 70 parts by weight of the modified coal gangue fine aggregate of this embodiment, 148 parts by weight of crushed stone coarse aggregate with a particle size of 15-20 mm, 6 parts by weight of 350-mesh shell powder, 0.85 parts by weight of polycarboxylic acid water reducer, and 4 parts by weight of polypropylene fiber with a length of 5 mm. Mix the above raw materials and stir evenly, then add mixing water according to a water-cement ratio of 0.41 and stir evenly to obtain 3D printing concrete material.
[0063] After printing the 3D printed concrete material prepared in this embodiment, a specimen was cut out of it, and then the 1d and 28d compressive strengths were tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). In addition, the fluidity of the 3D printed concrete material was tested according to the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005), and the results were: 1d compressive strength = 8.04MPa, 28d compressive strength = 44.21MPa, and fluidity = 16.2cm.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process for 3D printing concrete material of coal gangue aggregate, characterized in that: The steps include: (1) immersing the coal gangue fine aggregate after calcination to remove organic matter into a saturated aluminum sulfate solution, separating the fine aggregate after standing, drying, immersing in anhydrous ethanol containing saturated ethyl orthosilicate and standing; after completion, separating the fine aggregate and drying to obtain coal gangue fine aggregate a; (2) spraying saturated lime water into the gangue fine aggregate a under stirring conditions, heating and keeping the formed wet material in a closed container, and calcining the material after the reaction is completed to obtain modified gangue fine aggregate; (3) Mix silicate cement, modified coal gangue fine aggregate, coarse aggregate, admixture, water reducer, and chopped fibers, then add water and mix evenly to obtain the 3D printing concrete material.
2. The preparation process of the gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (1), the ratio of the coal gangue fine aggregate to the saturated aluminum sulfate solution is 1g: 5-20ml; Optionally, in step (1), the particle size of the coal gangue fine aggregate is 1-2 mm; Optionally, in step (1), the fine aggregate is separated after standing for not less than 30 minutes; Optionally, in step (1), the drying temperature is 60-100° C. and the drying time is 20-30 min.
3. The preparation process of the gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (1), the ratio of the fine aggregate to anhydrous ethanol is 1g: 5-20ml; Optionally, in step (1), the standing time in the anhydrous ethanol is not less than 40 minutes; Optionally, in step (1), the drying temperature is 50-70° C. and the drying time is 10-15 min.
4. The preparation process of the gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (2), the ratio of the coal gangue fine aggregate a to saturated lime water is 1g:0.45-0.6ml.
5. The preparation process of gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (2), the heating temperature is 60-80° C. and the insulation time is 8-10 hours.
6. The preparation process of gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (2), the calcination temperature is 600-720° C. and the calcination time is 1-1.5 hours.
7. The preparation process of gangue aggregate 3D printing concrete material according to claim 1, characterized in that: In step (3), the proportions of the silicate cement, modified coal gangue fine aggregate, coarse aggregate, admixture, water reducer and chopped fibers are 30-50 parts by weight: 60-92 parts by weight: 125-180 parts by weight, 4-10 parts by weight: 0.7-1.1 parts by weight: 5-7 parts by weight, and the water is added at a water-cement ratio of 0.38-0.
45.
8. The preparation process of the gangue aggregate 3D printing concrete material according to any one of claims 1 to 7, characterized in that: In step (3), the admixture includes at least one of mineral powder, shell powder, modified waste red brick powder, and waste glass powder; Optionally, in step (3), the admixture has a fineness of 200-350 mesh; Optionally, in step (3), the water reducer includes any one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a lignin sulfonate water reducer; Furthermore, in step (3), the chopped fibers include at least one of polyethylene fibers, polypropylene fibers, polyvinyl alcohol fibers, polyacrylonitrile fibers, and basalt fibers; Furthermore, in step (3), the length of the chopped fibers is 3 to 10 mm.
9. The preparation process of the gangue aggregate 3D printing concrete material according to claim 8, characterized in that: The modified waste red brick powder is prepared by the following method: placing the waste red brick powder in saturated lime water, separating the waste red brick powder after sufficient absorption, then adding aluminum nitrate solution and stirring evenly, and drying the obtained mixture to obtain the modified waste red brick powder.
10. The preparation process of gangue aggregate 3D printing concrete material according to claim 9, characterized in that: The ratio of the waste red brick powder to saturated lime water is 1g: 10-30ml; optionally, the waste red brick powder is placed in the saturated lime water and then left to stand for 20-30min, so that the red brick powder can fully absorb the saturated lime water; Optionally, the ratio of the waste red brick powder to the aluminum nitrate solution is 1g: 0.4-0.6ml; Optionally, the mass fraction of the aluminum nitrate solution is 2-5%; Optionally, the drying temperature is 60-80° C., and the drying is performed at this temperature to a constant weight.
Citation Information
Cited By
All-solid waste concrete as well as preparation method and application thereof
CN119874255A
